Covalent 2D-Engineering of Graphene by Spatially Resolved Laser Writing/Reading/Erasing - Edelthalhammer, Konstantin; Dasler, Daniela; Jurkiewicz, Lisa; Nagel, Tamara; Al-Fogra, Sabrin; Hauke, Frank; Hirsch, Andreas; Al-Fogra, Sabrin (Angewandte Chemie International Edition, 2020)
We report a facile and efficient method for the covalent 2D-patterning of monolayer graphene via laser irradiation. We utilized the photo-cleavage of dibenzoylperoxide (DBPO) and optimized the subsequent radical additions to non-activated graphene up to that level where controlled covalent 2D-patterning of graphene initiated by spatially resolved laser writing is possible. The covalent 2D-functionalization of graphene, which is monitored by scanning Raman microscopy (SRM) is completely reversible. This new concept enables write/read/erase control over the covalent chemical information stored on the graphene surface.
CRIS-Team Scopus Importer:2020-10-16
Keywords: covalent functionalization; covalent patterning; graphene; Raman spectroscopy; write/read/erase

Moiré Lattice of Twisted Bilayer Graphene as Template for Non-Covalent Functionalization - Dierke, Tobias; Wolff, Stefan; Gillen, Roland; Eisenkolb, Jasmin; Nagel, Tamara; Maier, Sabine; Kivala, Milan; Hauke, Frank; Hirsch, Andreas; Maultzsch, Janina (Angewandte Chemie International Edition, 2025)
We present a novel approach to achieve spatial variations in the degree of non-covalent functionalization of twisted bilayer graphene (tBLG). The tBLG with twist angles varying between 5° and 7° was non-covalently functionalized with 1,4,5,8,9,11-hexaazatriphenylenehexacarbonitrile (HATCN) molecules. Our results show a correlation between the degree of functionalization and the twist angle of tBLG. This correlation was determined through Raman spectroscopy, where areas with larger twist angles exhibited a lower HATCN peak intensity compared to areas with smaller twist angles. We suggest that the HATCN adsorption follows the moiré pattern of tBLG by avoiding AA-stacked areas and attach predominantly to areas with a local AB-stacking order of tBLG, forming an overall ABA-stacking configuration. This is supported by density functional theory (DFT) calculations. Our work highlights the role of the moiré lattice in controlling the non-covalent functionalization of tBLG. Our approach can be generalized for designing nanoscale patterns on two-dimensional (2D) materials using moiré structures as a template. This could facilitate the fabrication of nanoscale devices with locally controlled varying chemical functionalit
Keywords: 2D materials; Graphene; Raman spectroscopy; Density functional calculations; Functionalization

Spatial Control of Graphene Functionalization by Patterning a 2D Substrate: Implications for Graphene Based van-der-Waals Heterostructures - Dierke, Tobias; Dasler, Daniela; Nagel, Tamara; Hauke, Frank; Hirsch, Andreas; Maultzsch, Janina (ACS Applied Nano Materials, 2022)
We present an experimental study on the degree of covalent functionalization of graphene exfoliated on top of hBN stripes on Si/SiO2as well as on other two-dimensional (2D) materials. The underlying substrate has a strong effect on the degree of functionalization of graphene. Our results indicate that the functionalization of graphene is less effective on hBN than on SiO2, as shown by higher defect-induced modes in the graphene Raman spectra on SiO2. Other underlying 2D materials like MoS2, WS2, and MoO3show less contrast in functionalization density than hBN or lead to even higher degree of functionalization than the Si/SiO2substrate. Patterning the underlying material is therefore a versatile method for spatially defined functionalization of graphene because it preserves the intrinsic high-quality properties of graphene, a clear advantage over other patterning approaches based on masks or introduction of defects. Our work shows that the rich variety of 2D materials offers numerous possibilities to integrate graphene with different degrees of functionalization into van-der-Waals heterostructures and devices.
CRIS-Team Scopus Importer:2022-05-13
Keywords: 2D materials; functionalization pattern; graphene; hBN; Raman spectroscopy; van-der-Waals heterostructures

Towards precision controlled 2D functional group patterning of graphene via laser writing - Nagel, Tamara; Wolff, Stefan; Feng, Sijia; Weber, Heiko B.; Maultzsch, Janina; Hauke, Frank; Hirsch, Andreas (Carbon, 2025)
We herein present a significant advance in the understanding of the reaction mechanisms and the influence of the laser “writing” parameters in the laser-triggered activation of dibenzoyl peroxides (DBPO) and the subsequent high-precision covalent patterning of functional groups on monolayer graphene. Our straightforward and versatile procedure allows a complete deconvolution of the laser-induced functional group grafting in the “writing” step from a competing functionalization in the corresponding Raman characterization by a full removal of the DBPO film after covalent group attachment. This allows an in-depth analysis and understanding of the underlying laser “writing” and “reading” parameters - laser power and irradiation time - and thus a precise control of the degree of functionalization. Furthermore, by optimizing these parameters, the lateral dimension limits of the individual graphene patterned structures can be scaled down to 1.5 μm, with the potential to further improve the pattern size to the nanoscale in combination with a lithographically etched mask approach.
CRIS-Team Scopus Importer:2025-05-23
Keywords: Covalent functionalization; Graphene chemistry; Laser writing; Photochemistry; Precision structuring; Spatial control